Late-onset right ventricular failure after continuous-flow left ventricular assist device implantation: case presentation and review of the literature. Issue 2 (August 2022) - Hatano, Masaru; Jimba, Takahiro; Fujiwara, Takayuki; Tsuji, Masaki; Bujo, Chie; Ishida, Junichi; Amiya, Eisuke; Kinoshita, Osamu; Ono, Minoru
Highlights: With the widespread use of implantable left ventricular assist device (LVAD), late-onset right ventricular failure (RVF) has become a serious problem. Aortic insufficiency and ventricular arrythmia are considered to be closely involved in the onset and progression of RVF. Late-onset RVF was significantly associated with increased mortality. Several predictors of late-onset RVF have been proposed such as preoperative left ventricular diastolic dimension < 64 mm, tricuspid valve annulus diameter ≥ 41 mm and so on. Optimization of volume status and the rotation speed of LVAD, and inotrope administration in severe cases are required for the management of late-onset RVF.Tricuspid ventricular replacement or tricuspid annulus plasty may be performed if tricuspid regurgitation is severe. Summary: With the widespread use of implantable left ventricular assist device (LVAD), right ventricular failure (RVF) has become a serious problem that becomes apparent several weeks or later after LVAD implantation. However, there are no marked preoperative signs of RVF. This is called late-onset RVF and is currently a major problem leading to long-term complications following implantable LVAD use. Pathogenically, this could be the result of left ventricular suction by LVAD that causes the septum shift to the left ventricular side. This causes a change in morphology of the right ventricle, resulting in impaired right ventricular function. Aortic insufficiency and ventricular arrhythmia, which are also important as long-term complications after LVAD implantation, are considered to be closely involved in the onset and progression of RVF. Once late-onset RVF develops, exercise capacity declines and inotrope administration may be required. Late-onset RVF was also reported to be significantly associated with increased mortality. Several predictors of RVF have been proposed such as preoperative left ventricular diastolic dimension <64 mm, tricuspid valve annulus diameter ≥41 mm, and so on. However, some reports identified no predictors. The basic treatment strategy for late-onset RVF is to optimize volume status by administering diuretics and ensuring inotrope as needed. β-blockers and antiarrhythmic agents often need to be reduced in terms of dosage or even discontinued because these might reduce right ventricular function. Although their efficacy is unclear, pulmonary vasodilators may be used to reduce right ventricular afterload. It is better to decrease the rotation speed of LVAD to minimize the displacement of the septum; however, this is often difficult because the required flow rate cannot be secured. Progress in the prevention and management of late-onset RVF is required because the number of patients who require longer-term LVAD support will increase with the spread of LVAD use as destination therapy. Graphical abstract: Image, graphical abstract